Peningkatan Kemampuan Komputerisasi Akuntansi Perusahaan Dagang Menggunakan “Accurate” - Lucia Ari Diyani; Huda Aulia Rahman; Indra Wijaya (Politeknik Negeri Sriwijaya, 2019)
The development of computerized accounting technology made the addition of accounting software developed. Everyone who is involved in the field of accounting is required to be able to operate computerized accounting. Accurate is one of the most frequently used apps by many companies in Indonesia, this can be seen from the number of job vacancies with criteria able to operate accurate. The purpose of this training was to improve the competence of computerized accounting, especially accurate. Not all vocational students recognize accurate as a practical and easy to operate application. Accurate is very important to be mastered by vocational students so they have value added to compete in the world of work. This training was part of community service. SMK Yapin was a school that is the target of training activities. The training provided includes: knowledge of features in the accurate software, initial database preparation in accurate software using advanced preparation, data entry process in sales module, data entry process in purchasing module, data entry process in cash module, bank and general journals, also checking the financial statements. The training was conducted in one day and divided into two sessions. The conclusion was that the training was very successful and add insight and skills for teachers and students of SMK Yapin.